Composite component and method for preparing the same
By designing an alternately laminated composite coating of aluminum-molybdenum nitrogen layer and titanium-silicon nitrogen layer on metal cutting tools, the shortcomings of the existing coatings in terms of strength, toughness, wear resistance and high temperature resistance are solved, and more efficient tool use and processing performance are achieved.
Patent Information
- Application Number
- CN202411041393.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The existing tool coatings for metal cutting processing still need to improve their strength, wear resistance and high temperature resistance integration performance, especially in high temperature environments that are prone to oxidation failure.
The design of composite components is adopted, and the coating includes alternately stacked aluminum-molybdenum nitrogen layers and titanium-silicon nitrogen layers. The aluminum-molybdenum nitrogen layers are located on the outermost side and are deposited by physical vapor deposition method to regulate the deposition parameters to form a double-gradient multi-layer structure.
It realizes the integrated performance of the coating with high strength, high wear resistance and high temperature oxidation resistance, and improves the service life and processing efficiency of the tool under various working conditions.
Smart Images

Figure CN118814112B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of tool coating for metal cutting, and more specifically, to a composite component and a preparation method thereof. Background Art
[0002] Tools used in metal cutting are usually protected by coating materials to increase tool life and processing efficiency; however, the current coating's toughness, wear resistance, and high temperature resistance still need to be further improved. Summary of the invention
[0003] The present application provides a composite component and a preparation method thereof, which can comprehensively improve the strength, toughness, wear resistance and high temperature resistance of the coating.
[0004] A first aspect of the present application provides a composite component, which includes a substrate and a coating, the coating including at least one aluminum-molybdenum-nitride layer and at least one titanium-silicon-nitride layer, the titanium-silicon-nitride layer being arranged on the surface of the substrate, the titanium-silicon-nitride layer and the aluminum-molybdenum-nitride layer being alternately stacked along the thickness direction of the coating, and the aluminum-molybdenum-nitride layer being located on the outermost side of the coating.
[0005] In some embodiments, the aluminum-molybdenum-nitrogen layer includes an atomic ratio of For the material, the Al atomic percentage x is 0.5~0.95, the Mo atomic percentage 1-x is 0.05~0.5, and the N atomic stoichiometric ratio range z is 0.5~1.
[0006] In some embodiments, the titanium silicon nitride layer comprises: For the material, the Ti atomic percentage y is 0.8~0.95, the Si atomic percentage 1-y is 0.05~0.2; the N atomic stoichiometric ratio range z is 0.5~1.
[0007] In some embodiments, the titanium silicon nitride layer is a multi-layer layer, and the thickness of the titanium silicon nitride layer gradually decreases in the direction from the substrate to the coating.
[0008] In some embodiments, the aluminum-molybdenum-nitrogen layer is a multilayer layer, and the thickness of the aluminum-molybdenum-nitrogen layer gradually increases in the direction from the substrate to the coating.
[0009] In some embodiments, the thickness of the aluminum-molybdenum-nitrogen layer is greater than or equal to 0.001 μm and less than 5 μm.
[0010] In some embodiments, the thickness of the titanium silicon nitride layer is greater than or equal to 0.001 μm and less than 5 μm.
[0011] In some embodiments, the coating has a thickness of 0.5 μm to 5 μm.
[0012] In some embodiments, the substrate includes at least one of cemented carbide, stainless steel, and cermet.
[0013] In some embodiments, the hardness of the coating is 35 GPa~40 GPa.
[0014] In some embodiments, the elastic modulus of the coating is 430 GPa~490 GPa.
[0015] In some embodiments, the coating has an anti-plastic deformation capability of The value is 0.25GP~0.30GP.
[0016] The second aspect of the present application provides a method for preparing a composite component, characterized in that:
[0017] providing a substrate;
[0018] The coating is deposited on the substrate by physical vapor deposition.
[0019] In some embodiments, the step of depositing a coating on the substrate using physical vapor deposition is
[0020] Steps include:
[0021] The titanium silicon nitrogen layer and the aluminum molybdenum nitrogen layer are alternately deposited by physical vapor deposition. The working gases are argon and nitrogen. The total working gas pressure in the deposition furnace is kept constant, and the argon Ar and nitrogen are gradually increased. Gas flow ratio, gradually decreasing The gas flow rate is adjusted, and the arc source current of the TiSi target is increased and the arc source current of the AlMo target is reduced in sequence, so as to gradually increase the thickness of the titanium silicon nitrogen layer and reduce the thickness of the aluminum molybdenum nitrogen layer.
[0022] In some embodiments, the physical vapor deposition method is cathode arc ion plating technology, and the deposition process parameters are substrate bias of 30-120 V, arc source current of TiSi target of 100-240 A, arc source current of AlMo target of 240-100 A, and working gas pressure of 0.5-5 Pa. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a schematic diagram of the structure of the composite component.
[0024] FIG2 is a graphical representation of the coating hardness and elastic modulus of the tool in Example 1 and Comparative Example 1;
[0025] FIG3 is a schematic diagram of comparative example 1 and the coating of the tool in comparative example 1.
[0026] 1. Matrix;
[0027] 2. Titanium silicon nitrogen layer;
[0028] 3. Aluminum-molybdenum-nitride layer. DETAILED DESCRIPTION
[0029] At present, coatings are usually provided on the surface of metal cutting tools to improve the tool life and processing efficiency, and the coating materials are mainly transition metal nitride coatings.
[0030] For example, TiSiN coating is an amorphous coating formed by introducing Si element into binary TiN coating. The nanocomposite structure coating covering the TiN grains has The amorphous phase effectively limits the growth of TiN cubic phase grains, and the fine grain strengthening effect gives the TiSiN coating ultra-high hardness (> 40 GPa) and wear resistance, making it an attractive candidate for hard protective coating materials. However, due to the high residual compressive stress caused by the dense structure of TiSiN, its relatively low toughness limits its service performance under intermittent and heavy-load processing conditions; in addition, in the case of low cutting fluid or dry high-speed processing of difficult-to-process materials such as heat-resistant alloys, the rapid temperature rise caused by the accumulation of a large amount of cutting heat on the front face of the blade, combined with the oxidation reaction of oxygen in the air, will aggravate the oxidation failure of the coated tool, and the high-temperature oxidation temperature of the TiSiN coating is limited (< 750 ℃), which also greatly limits the performance of its high hardness and wear resistance. Therefore, how to modify the TiSiN coating has attracted people's attention.
[0031] In the related technology, the high-strength and tough nanocomposite coating with a multilayer structure of a multilayer AlTiN / TiSiN support layer and a TiSiN working layer has a low Al atomic ratio in the AlTiN layer and is therefore not suitable for high-temperature service environments. The protective layer is less formed, and the improvement of the anti-oxidation performance of the coating is limited. In addition, the improvement of the intrinsic toughness of the coating is limited by inhibiting the expansion of cracks through the construction of a multi-layer structure. The bonding strength of the coating is improved by building a multi-layer structure. In addition, elements such as Me=Cr, Ta, Nb, and Mo also help to improve the intrinsic toughness of the coating. However, the Al content of the coating is only , the improvement of the overall high-temperature oxidation resistance of the coating is still limited.
[0032] In the related technologies, it is impossible to achieve the integration of coating toughness, wear resistance and high temperature resistance. The toughness, oxidation resistance and friction reduction effect of TiSiN coatings for cutting tools need to be further improved.
[0033] In the present application, the coating includes at least one aluminum-molybdenum-nitride layer and at least one titanium-silicon-nitride layer, which can overcome the shortcomings of traditional TiSiN coatings that cannot have both high hardness and toughness and have insufficient resistance to high-temperature oxidation. The coating has high strength, high toughness, high wear resistance and high-temperature oxidation resistance.
[0034] In a first aspect, the present application provides a composite component, the composite component includes a substrate and a coating, the coating includes at least one aluminum-molybdenum-nitride layer and at least one titanium-silicon-nitride layer, the titanium-silicon-nitride layer is arranged on the surface of the substrate, the titanium-silicon-nitride layer ( layer) and the aluminum molybdenum nitride layer ( The aluminum, molybdenum and nitrogen layers are alternately stacked along the thickness direction of the coating, and the aluminum, molybdenum and nitrogen layers are located on the outermost side of the coating.
[0035] The coating of the present application is a double gradient multilayer composite Coating, composite components can be considered as dual-structure multi-layer composite structure coating tools;
[0036] Firstly, the cubic TiSiN template layer is used to stabilize the AlMoN sublayer to achieve coherent epitaxial growth. The coherent interface strengthening effect improves the comprehensive mechanical properties of the coating. Secondly, combined with The superhard properties of the layer The high temperature oxidation resistance of the layer, the introduction of Mo element with high valence electron concentration can improve the intrinsic toughness of the coating, and the The self-lubricating phase can significantly reduce the cutting friction resistance;
[0037] Furthermore, along the thickness direction, from the inside to the outside of the substrate surface, The thickness of the modulation layer (ie, titanium silicon nitride layer) increases. The dual gradient structure in which the modulation layer (i.e., aluminum-molybdenum-nitrogen layer) is reduced and the N content changes from a substoichiometric ratio to a stoichiometric ratio can achieve a gradual change in performance from tough inside to hard outside, which can ensure good film-base bonding strength and further improve the toughness of the coating.
[0038] In summary, the present application can realize the integrated characteristics of coating toughness, wear resistance and high temperature oxidation resistance, and has good competence in multiple working conditions of finishing, semi-finishing and heavy-load roughing of difficult-to-cut materials such as stainless steel, titanium alloy and high-temperature alloy.
[0039] In some embodiments, the aluminum-molybdenum-nitrogen layer includes an atomic ratio of For the material, the Al atomic percentage x is 0.5~0.95, the Mo atomic percentage 1-x is 0.05~0.5, and the N atomic stoichiometric ratio range z is 0.5~1.
[0040] In some embodiments, the titanium silicon nitride layer comprises: For the material, the Ti atomic percentage y is 0.8~0.95, the Si atomic percentage 1-y is 0.05~0.2; the N atomic stoichiometric ratio range z is 0.5~1.
[0041] In some embodiments, the titanium silicon nitrogen layer is multi-layered, such as 2 layers, 3 layers, 4 layers, 5 layers or even more layers. For example, the composite component includes a substrate, a titanium silicon nitrogen layer, an aluminum molybdenum nitrogen layer, a titanium silicon nitrogen layer, and an aluminum molybdenum nitrogen layer stacked in sequence along the thickness.
[0042] Optionally, in a direction from the substrate to the coating, the thickness of the titanium silicon nitride layer gradually decreases.
[0043] In some embodiments, the aluminum-molybdenum-nitrogen layer is a multi-layer, such as 2 layers, 3 layers, 4 layers, 5 layers or even more layers.
[0044] Optionally, the thickness of the aluminum-molybdenum-nitrogen layer gradually increases in a direction from the substrate to the coating.
[0045] For example, as shown in Fig. 1, the composite component includes a substrate 1 and a coating, and the coating includes a multilayer titanium silicon nitrogen layer 2 and an aluminum molybdenum nitrogen layer 3. The arrow direction in the figure indicates the thickness direction.
[0046] In some embodiments, the thickness of the aluminum-molybdenum-nitrogen layer is greater than or equal to 0.001 μm and less than 5 μm.
[0047] In some embodiments, the thickness of the titanium silicon nitride layer is greater than or equal to 0.001 μm and less than 5 μm.
[0048] In some embodiments, the coating has a thickness of 0.5 μm to 5 μm.
[0049] In some embodiments, the substrate comprises at least one of cemented carbide, stainless steel and metal ceramic.
[0050] One, the specific material can be materials known in the art and is not specifically limited in this application.
[0051] In some embodiments, the hardness of the coating is 35 GPa~40 GPa.
[0052] In some embodiments, the elastic modulus of the coating is 430 GPa~490 GPa.
[0053] In some embodiments, the coating has an anti-plastic deformation capability of The value is 0.25GP~0.30GP.
[0054] A second aspect of the present application provides a method for preparing a composite component, comprising providing a substrate;
[0055] The coating is deposited on the substrate by physical vapor deposition.
[0056] In some embodiments, the step of depositing a coating on the substrate using a physical vapor deposition method comprises:
[0057] The titanium silicon nitrogen layer and the aluminum molybdenum nitrogen layer are alternately deposited by physical vapor deposition. The working gases are argon and nitrogen. The total working gas pressure in the deposition furnace is kept constant, and the argon Ar and nitrogen are gradually increased. Gas flow ratio, gradually decreasing The gas flow rate is adjusted, and the arc source current of the TiSi target is increased and the arc source current of the AlMo target is decreased in sequence, so as to gradually increase the thickness of the titanium silicon nitrogen layer and decrease the thickness of the aluminum molybdenum nitrogen layer.
[0058] By adjusting the total working gas pressure in the deposition furnace to remain constant, argon Ar and nitrogen are gradually added. Gas flow ratio, gradually decreasing The gas flow rate is adjusted so that the N stoichiometric ratio increases from the inside to the outside.
[0059] In some embodiments, the physical vapor deposition method is cathode arc ion plating technology, and the deposition process parameters are substrate bias of 30-120 V, arc source current of TiSi target of 100-240 A, arc source current of AlMo target of 240-100 A, and working gas pressure of 0.5-5 Pa.
[0060] Alternating deposition During the coating process, the arc source current of the TiSi target is increased while the arc source current of the AlMo target is reduced. The arc source current of the TiSi target varies in the range of 100~240 A, and the arc source current of the AlMo target varies in the range of 240~100 A. Depending on the performance of the coating and application requirements, the range of increase / decrease of the arc source current of the above targets can be changed accordingly.
[0061] In some embodiments, the substrate may be a metal tool, such as at least one of a cemented carbide substrate, a stainless steel substrate, and a metal ceramic substrate, wherein the cemented carbide may be prepared by powder metallurgy.
[0062] For example, the matrix can be prepared by the following method:
[0063] A cemented carbide matrix and / or a metal ceramic matrix is prepared by powder metallurgy, and a sintered matrix blank is subjected to deep processing to obtain a deep-processed tool matrix;
[0064] The tool substrate after deep processing is cleaned and dried, and subjected to argon ion bombardment etching activation treatment to obtain a pre-treated tool substrate.
[0065] Exemplarily, the deep processing includes at least one of grinding, sandblasting and polishing.
[0066] Physical vapor deposition is used to alternately deposit on the pre-treated tool substrate and coating, and control the total working pressure in the furnace to remain unchanged, gradually increase Gas flow rate, i.e. gradually decreases The gas flow rate is increased, and at the same time, the arc source current of the TiSi target is increased and the arc source current of the AlMo target is reduced, that is, the modulation layer thickness of TiSiN is gradually increased and the modulation layer thickness of AlMoN is reduced.
[0067] Example 1
[0068] A double-structure multi-layer composite coating tool, from the inside to the outside are the tool base, The total thickness of the coating is 3.15 μm; wherein the double-structure multi-layer composite structure coating The atomic ratio of the layer is (0.7~1 represents that the stoichiometric ratio of the N content of the coating from the inside to the outside of the substrate surface and the normalized value of the metal gradually changes from 0.7 to 1); The atomic ratio of the layer is ; At the same time, from the inside out Layer and The modulation ratio of the layer gradually decreases from 2:1 to 1:2, and accordingly, from inside to outside Layer and The layer thickness ratio gradually decreases from 2:1 to 1:2.
[0069] The tool base is a carbide strip and a stainless steel turning insert.
[0070] The preparation method of the dual-gradient multi-layer composite structure coating tool of this embodiment has the following specific steps:
[0071] (1) Using powder metallurgy method to process WC, Co, TaC, The powders are wet-milled, spray-dried, pressed, and sintered into blanks, and then subjected to a series of mechanical deep processing to obtain tool base abrasives; the tool base abrasives are cleaned before coating to achieve decontamination requirements and good surface quality;
[0072] (2) Then it is sent to the coating equipment for high-energy argon ion etching activation treatment: the working gas Ar is introduced and the pressure in the furnace is set to ; Turn on the bias power supply, the voltage is 180 V; turn on the ion source current to 150 A, and the etching time is 35 min.
[0073] (3) Alternate deposition on the tool substrate using cathode arc evaporation ion plating technology Layer and Layer: Through the working gas and Ar, and the total working pressure in the furnace was maintained at 3.5 Pa, the bias voltage was set to 60 V, the workpiece turntable speed was 40% (~1.6 r / min), and the AlMo target and TiSi target were turned on at the same time. The initial arc source current of the AlMo target was 200 A, and the final current was 100 A; the initial arc source current of the TiSi target was 100 A, and the final current was 200 A; during the deposition process The flow rate was gradually increased from 900 sccm at the beginning to 1200 sccm at the end of deposition, and Ar was reduced from 300 sccm at the beginning to 0 sccm at the end. The total deposition time was 300 min.
[0074] (4) Turn off all arc sources, bias voltage, heating power, and gas, and cool naturally under vacuum until the temperature inside the furnace is less than 200 °C. The coating is completed.
[0075] Example 2
[0076] A double-structure multi-layer composite coating tool was prepared by a method similar to that in Example 1, wherein from the inside to the outside, the tool substrate is formed, coating, the total coating thickness is 3.28 μm;
[0077] Among them, the above-mentioned double-structure multi-layer composite coating The atomic ratio of the layer is The atomic ratio of the layer is At the same time, from the inside out Layer and The modulation ratio of the layer gradually decreases from 3:2 to 2:3, and accordingly, from inside to outside Layer and The layer thickness ratio gradually decreases from 3:2 to 2:3.
[0078] Example 3
[0079] A double-structure multi-layer composite coating tool was prepared by a method similar to that in Example 1, wherein from the inside to the outside, the tool substrate is formed, coating, the total coating thickness is 3.17 μm;
[0080] Among them, the above-mentioned double-structure multi-layer composite coating The atomic ratio of the layer is The atomic ratio of the layer is At the same time, from the inside out Layer and The modulation ratio of the layer gradually decreases from 3:1 to 1:1, and accordingly, from inside to outside Layer and The thickness ratio of the layers gradually decreases from 3:1 to 1:1.
[0081] Comparative Example 1
[0082] A double-structure multilayer composite coating tool was prepared by a method similar to that in Example 1, and a TiSiN single-layer uniform coating was prepared by the same deposition technology and process parameters. The coating thickness was 3.25 μm.
[0083] Performance Testing
[0084] The hardness and elastic modulus of the coatings of Example 1 and Comparative Example 1 were measured using a nanoindenter produced by Anton Paar. The results are shown in FIG2 .
[0085] Compared with the mechanical properties of the coating in Comparative Example 1 (hardness is ~ 38.6 GPa, elastic modulus is ~ 500.5 GPa, The hardness of the coating of Example 1 remained close (~ 38.4 GPa), while the elastic modulus decreased (~ 439.6 GPa), thus having a higher value (~ 0.29 GP), i.e., it has better resistance to plastic deformation.
[0086] The toughness of the coating was qualitatively evaluated using a Mitutoyo MVK-H1 Vickers hardness tester, and the results are shown in FIG3 . Comparative Example 1 has obvious diagonal cracks on the coating surface, while Example 1 has no diagonal cracks, demonstrating that it has better toughness.
[0087] The dual-structure multi-layer composite coating tools of Examples 1, 2, and 3 and the coating tool of Comparative Example 1 were subjected to cutting verification under the same cutting processing conditions as follows. The specific cutting parameters are as follows:
[0088] Processing parameter 1:
[0089] Processing material SUS316 stainless steel
[0090] Cutting speed
[0091] Feed
[0092] Cutting depth
[0093] Cooling method: dry cooling.
[0094] Processing parameters 2:
[0095] Processing material SUS316 stainless steel
[0096] Cutting speed
[0097] Feed
[0098] Cutting depth
[0099] Cooling method: dry cooling.
[0100] The performance evaluation of coated tools adopts two comparison standards: same life and full life. The same life means the same cutting time, and the wear failure forms of the front and rear blades of the tools are compared; after the full life, the uniform wear amount VB of the rear blade reaches 0.25 mm, or the crescent crater of the front blade of the tool is worn to the edge, and the machine tool vibrates greatly. Under processing parameter 1, after 15 minutes of continuous turning, the VB values of the rear blade wear of the coated blades in Examples 1, 2, and 3 are 0.129, 0.112, and 0.105 mm, respectively, as shown in Table 1. The VB value of the rear blade of the tool in Comparative Example 1 reached 0.143 mm. Under the full life, the cutting time of complete failure of the coated blades in Examples 1, 2, and 3 and the coated blades in Comparative Example 1 are 29, 31, 33, and 26 minutes, respectively. The life of the coated blades in Examples 1, 2, and 3 is increased by 11%, 19%, and 27% respectively compared with the comparative coated tools.
[0101] Table 1 Coated blade life of Examples 1, 2, 3 and Comparative Example 1
[0102]
[0103] Under machining parameter 2, after 10 min of continuous turning, the flank wear VB values of the coated inserts in Examples 1, 2, and 3 were 0.135, 0.128, and 0.145 mm, respectively, as shown in Table 2. The flank VB value of the tool in Comparative Example 1 reached 0.169 mm. Under full life, the cutting time of complete failure of the coated inserts in Examples 1, 2, and 3 and the coated insert in Comparative Example 1 was 19, 21, 17, and 15.5 min, respectively. The life of the coated inserts in Examples 1, 2, and 3 was increased by 22%, 35%, and 10%, respectively, compared with the comparative coated tool.
[0104] Table 2 Coated blade life of Examples 1, 2, 3 and Comparative Example 1
[0105]
[0106] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A composite component, characterized in that: include: matrix; as well as The coating comprises at least one aluminum-molybdenum-nitride layer and at least one titanium-silicon-nitride layer, wherein the titanium-silicon-nitride layer is disposed on the surface of the substrate, the titanium-silicon-nitride layer and the aluminum-molybdenum-nitride layer are alternately stacked along the thickness direction of the coating, and the aluminum-molybdenum-nitride layer is located on the outermost side of the coating. Wherein, the aluminum-molybdenum-nitrogen layer comprises the following atomic ratios: For materials, the Al atomic percentage x is 0.5~0.95, the Mo atomic percentage 1-x is 0.05~0.5, and the N atomic stoichiometric ratio range z is 0.5~1; The titanium silicon nitride layer is a multilayer, and the aluminum molybdenum nitride layer is a multilayer. The thickness of the titanium silicon nitride layer formed sequentially from the inside to the outside of the substrate surface increases, and the thickness of the aluminum molybdenum nitride layer decreases.
2. The composite component according to claim 1, characterized in that The titanium silicon nitrogen layer includes the following components in atomic ratio: For materials, the atomic percentage y of Ti is 0.8~0.95, and the atomic percentage 1-y of Si is 0.05~0.2; The stoichiometric ratio of N atoms varies from z to 0.5~1.
3. The composite component according to claim 1, characterized in that The thickness of the aluminum-molybdenum-nitrogen layer is greater than or equal to 0.001 μm and less than 5 μm; and / or The thickness of the titanium silicon nitride layer is greater than or equal to 0.001 μm and less than 5 μm.
4. The composite component according to claim 1, characterized in that The coating has a thickness of 0.5 μm to 5 μm.
5. The composite component according to claim 1, characterized in that The substrate includes at least one of cemented carbide, stainless steel and metal ceramic.
6. The composite component according to claim 1, characterized in that The hardness of the coating is 35 GPa to 40 GPa; and / or The elastic modulus of the coating is 430 GPa~490 GPa.
7. A method for preparing a composite component according to any one of claims 1 to 6, It is characterized in that include: providing a substrate; The coating is deposited on the substrate by physical vapor deposition.
8. The preparation method according to claim 7, characterized in that: The step of depositing a coating on the substrate by physical vapor deposition comprises: The titanium silicon nitrogen layer and the aluminum molybdenum nitrogen layer are alternately deposited by physical vapor deposition. The working gases are argon and nitrogen. The total working gas pressure in the deposition furnace is kept constant, and the argon Ar and nitrogen are gradually increased. Gas flow ratio, gradually decreasing The gas flow rate is adjusted, and the arc source current of the TiSi target is increased and the arc source current of the AlMo target is decreased in sequence, so as to gradually increase the thickness of the titanium silicon nitrogen layer and decrease the thickness of the aluminum molybdenum nitrogen layer.
9. The preparation method according to claim 8, characterized in that: The physical vapor deposition method is a cathode arc ion plating technology, and the deposition process parameters are: substrate bias voltage is 30-120 V, arc source current of TiSi target is 100-240 A, arc source current of AlMo target is 240-100 A, and working gas pressure is 0.5-5 Pa.
Citation Information
Patent Citations
High-toughness hard coating, preparation process and application thereof and cutter
CN117364021A